Analisis Gambaran Kondisi Pembangunan Dalam Film "13 Bom di Jakarta" : Tinjauan Keterbelakangan Pembangunan - Robby Dwi Widiyanto; Yoga Septa Nurivandi; Muhamad Feri Herdiansyah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research focuses on analyzing the depiction of development in the film "13 Bombs in Jakarta". The act of rebellion through bomb terror carried out by a terrorist group depicts a social setting that describes the development conditions in that place. Andre Gunder Frank's theory is used as an analytical tool in describing the social setting in the film. In the realization of development carried out as an effort to improve social welfare, quality of life and eradicate poverty, the government plays a very important role in realizing this dream. The policies created should provide benefits to the communities targeted by these targets. If there is a discrepancy between policies and the benefits received, an attitude of distrust from the public will arise. There could even be acts of terror as a form of public dissatisfaction. The research method in this paper uses a descriptive qualitative method. Data collection is divided into two types, namely primary data and secondary data. The purpose of this paper is to analyze the conditions in the development context in the film "13 Bombs in Jakarta".